Workshop on the design and use of clinical trials with multiple endpoints, with a focus on prevention of RSV - O. Prunas; J. Willemsen; J.L. Warren; L. Bont; J.L. Schwartz; J. Atwell; E. Begier; N. Dean; I. Hirsch; R. Karron; K. Klugman; R. Kramer; et al. (Vaccine: X, 2024)
A meeting held in Lisbon, Portugal, in February 2023 focused on critical aspects of clinical trial design for respiratory syncytial virus (RSV) preventative therapies. The meeting addressed two primary areas: enhancing the efficiency and success of randomized controlled trials (RCTs) for RSV preventative therapies and designing RCTs to better inform post-licensure decision-making. Topics included the selection of primary endpoints, innovative approaches to incorporating multiple endpoints and historical data, and the challenges and benefits of sequential trial designs. The discussion also touched on meta-regression models for obtaining more robust, context-specific estimates of vaccine efficacy. Overall, the meeting underscored the importance of balancing efficiency and robustness in RSV vaccine trial design, while recognizing the need for further discussions involving regulatory and advisory bodies.